Perubahan Prosesi Penobatan Depati Di Desa Koto Tengah Kec. Tanah Kampung Dalam Upacara Budaya Kenduri Sko (1990-2020) - Indra Muhammad Gandi; Najmi Najmi (Jurusan Sejarah FIS UNP, 2023)
The skills to think historical research capabilities (skills to build historical significance) are the first skills that must be possessed by students, thinking historical research capabilities (skills to build historical significance) are generally a number of steps or scientific processes in history. one way to improve students' skills in building historical significance is by using interactive media packaged in a mnemonic dictionary, therefore this study aims to, 1. to find out whether the use of an e-mnemonic dictionary can improve students' historical significance skills. 2. The practicality of the e-mnemonic dictionary learning resources as a whole is in the practical category. 3. Knowing the effectiveness of e-mnemonic dictionary learning resources in improving skills in building historical significance. The research method is Research and Development (R&D), using the Thiagarajan 4D development model which consists of 3 stages of development namely definition, planning (design), and development ( develop). The results of the study show that, in general, the feasibility of e-mnemonic learning resources is feasible and able to help improve skills in building historical significance. keywords: interactive learning resources, e-mnemonic dictionaries, historical significance building skills, historical research capabilities.